Soil organic matter pools in a tropical savanna under agroforestry system in Northeastern Brazil - Leite,Luiz Fernando Carvalho (2014)
This study aimed at quantifying total organic carbon stocks and its pools in Acrisol under agroforestry systems with six (AFS6) and thirteen years old (AFS13), slash-and-burn agriculture (SBA) and savanna native forest (SNF) in northeastern Brazil. Soil samples were collected at 0-0.05 m, 0.05-0.10 m, 0.10-0.20 m and 0.20-0.40 m depths in the dry and rainy seasons to evaluate total organic carbon (TOC) stocks and labile carbon (LC), fulvic acid fraction (C-FAF), humic acid fraction (C-HAF), humin (C-HF) and microbial biomass carbon (Cmic) contents. Additionally, carbon management index (CMI) was determined. Higher TOC stocks (97.7 and 81.8 Mg ha-1 for the 0-0.40 m depth in the dry and rainy seasons, respectively) and LC, humic substances and Cmic contents were observed in the AFS13 in all the depths. CMI also was higher in the AFS13 (0-0. 05 m: 158 and 86; 0.05-0.10 m: 171 and 67, respectively for the dry and rainy seasons) especially when compared to the SBA (0-0.05 m: 5.6 and 5.4; 0.05-0.10 m: 5.3 and 5.8, respectively for dry and rainy seasons). The agroforestry systems increased soil quality through the conservation of organic matter and can be considered an excellent strategy to assurance sustainability in tropical soil of Northeastern Brazil